Pengaruh Konten Review, Kualitas Produk, Dan Gaya Hidup Terhadap Minat Mahasiswa Menggunakan Fashion Produk Lokal - Dhana Berlyan Reksa Dewa; Hartirini Warnaningtyas; Choirum Rindah Istiqaroh (Universitas Merdeka Madiun, 2023)
This study aims to examine and determine the effect of review content, product quality, and lifestyle on students' interest in using local products fashion. The population in this study were students of the Faculty of Economics, Merdeka Madiun University, users of local products fashion. The sample size in this study was 152 people. The method used in sampling is purposive sampling. The research instrument used a questionnaire. Data analysis techniques used the classical assumption test, multiple linear regression analysis, analysis of the coefficient of determination, and hypothesis testing using the t test and F test. The results showed that the content review variable partially had a significant effect on students' interest in using local products fashion, product quality variables partially has a significant effect on students' interest in using local products fashion, lifestyle variables partially have a significant effect on students' interest in using local products fashion, and simultaneously the review content variables, product quality, and lifestyle have a significant effect on students' interest in using local products fashion.